2021
DOI: 10.1007/s11845-021-02653-9
|View full text |Cite
|
Sign up to set email alerts
|

The role of unconventional T cells in COVID-19

Abstract: COVID-19 is a respiratory disease caused by the severe acute respiratory syndrome coronavirus 2 (SARS-CoV-2). It was first documented in late 2019, but within months, a worldwide pandemic was declared due to the easily transmissible nature of the virus. Research to date on the immune response to SARS-CoV-2 has focused largely on conventional B and T lymphocytes. This review examines the emerging role of unconventional T cell subsets, including γδ T cells, invariant natural killer T (iNKT) cells and mucosal ass… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2
2
1

Citation Types

1
6
0
1

Year Published

2021
2021
2023
2023

Publication Types

Select...
8

Relationship

0
8

Authors

Journals

citations
Cited by 10 publications
(8 citation statements)
references
References 96 publications
1
6
0
1
Order By: Relevance
“…As a result of high-resolution mapping of thousands of γδ T lymphocytes from patients with cancer or COVID-19, we were able to gain a wealth of information about γδ T lymphocyte differentiation dynamics at the single-cell scale. As reviewed in this series, the role of human γδ T cells in viral infections is highly investigated and debated in the context of SARS-CoV-2 infection [45][46][47][48]. Here, we found in PBMC of COVID-19 patients that γδ T lymphocytes were decreased compared to control samples, a finding consistent with flow cytometry studies [16,20,49,50].…”
Section: Discussionsupporting
confidence: 87%
“…As a result of high-resolution mapping of thousands of γδ T lymphocytes from patients with cancer or COVID-19, we were able to gain a wealth of information about γδ T lymphocyte differentiation dynamics at the single-cell scale. As reviewed in this series, the role of human γδ T cells in viral infections is highly investigated and debated in the context of SARS-CoV-2 infection [45][46][47][48]. Here, we found in PBMC of COVID-19 patients that γδ T lymphocytes were decreased compared to control samples, a finding consistent with flow cytometry studies [16,20,49,50].…”
Section: Discussionsupporting
confidence: 87%
“…Vγ9δ2T cells give rise to the main subtype of peripheral γδT cells. Virus-activated γδT cells could trigger a series of antiviral responses including release of cytokines (including IFN-γ, TNF-α, and IL-17), restriction of viral replication, Du et al 10.3389/fmicb.2022.936272 and cytolysis of virus-infected cells (Jouan et al, 2020;Lei et al, 2020;Yazdanifar et al, 2020;Orumaa and Dunne, 2022). Multiple mechanisms have been proposed for the recognition of SARS-CoV-2 by γδT cells.…”
Section: Introductionmentioning
confidence: 99%
“…Further we also analyzed hub genes and cytokine storm related genes of prioritized circRNAs. Orumaa and co-authors revealed that severity of COVID-19 is linked to cytokine storm, which occurs when levels of inflammatory mediators such as IL-7, IL-10, and MIP are up-regulated [ 81 ]. Hassan et al, revealed the connection of IL-17 to critically sick patients infected with SARS-CoV-2 [ 82 ].…”
Section: Discussionmentioning
confidence: 99%